2017
DOI: 10.3390/ijerph14101139
|View full text |Cite
|
Sign up to set email alerts
|

WHO Environmental Noise Guidelines for the European Region: A Systematic Review on Environmental Noise and Permanent Hearing Loss and Tinnitus

Abstract: Background: Hearing loss is defined as worsening of hearing acuity and is usually expressed as an increase in the hearing threshold. Tinnitus, defined as “ringing in the ear”, is a common and often disturbing accompaniment of hearing loss. Hearing loss and environmental exposures to noise are increasingly recognized health problems. Objectives: The objective was to assess whether the exposure-response relationship can be established between exposures to non-occupational noise and permanent hearing outcomes suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 40 publications
0
97
0
4
Order By: Relevance
“…Noise generated by ventilation systems constitutes a limited part of subway noise but lasts the longest. Long-term exposure to environmental noise can have a number of health effects [309,310]. The primary sources of subway noise include subway operation, public broadcasting, and human activities.…”
Section: Noisementioning
confidence: 99%
“…Noise generated by ventilation systems constitutes a limited part of subway noise but lasts the longest. Long-term exposure to environmental noise can have a number of health effects [309,310]. The primary sources of subway noise include subway operation, public broadcasting, and human activities.…”
Section: Noisementioning
confidence: 99%
“…One of the major original features of the present approach rests upon the construction of the point sources for each calculation point and not for all the receivers points, as depicted at figure 5. This allows to reduce the amount of point sources required at each calculation point, in respect of equations (2). Besides, for the same purpose of limiting the amount of calculations, only sound sources located within a critical radius centred on each calculation point are considered.…”
Section: Point Source Generationmentioning
confidence: 99%
“…Considering noise exposure, many works have shown that it can be associated to many adverse health outcomes, such as hearing impairments and tinnitus [2], cardiovascular and metabolic repercussions [3], learning impairment [4], sleep disorders [5], annoyance [6]. .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of the World Health Organization (WHO) [9] conclude that the diseases related to the effect of noise on people are producing a huge loss in healthy life years, in addition to the annoyance it causes to neighbors [10]. For instance, permanent hearing loss and tinnitus are associated with noise exposure [8,11].Moreover, it has been argued that noise can lead to adverse birth outcomes, as stated in [12], a work focused on studying the effects of aircra noise on preterm births. More specifically, RTNone of the main noise sources in urban areas-increases tiredness and disturbs the sleep pattern [13].…”
Section: Introductionmentioning
confidence: 99%